(untitled) (Progressive Agriculture, 2020)
The main purpose of this study was to determine and describe some socio-demographic character of farmers, the extent of adoption of climate change adaptation practices, explore relationship between selected characteristics and climate change adaptation practices as well as determining the problem faced by the farmers for climate change adaptation. Data were collected using interview schedule from a sample of 96 farmers (exactly 30% of population) out of 320 farmers. For selection of the sample of the study simple random sampling technique was followed. Besides the usual descriptive statistical parameter, Pearson’s Product Moment Correlation Coefficient (r) was used for the statistical analysis. Adoption of climate change adaptation practices was determined on 23 selected practices. For comparative analysis of adoption of climate change adaptation practices by the farmers in individual practices “Adoption of Climate Change Adaptation Practices Index (ACAPI)” was calculated. The highest proportion of the farmers adopt ‘Pit crop in homestead’ (ACAPI= 230.7) as climate change adaptation practice. The lowest adopted practice for climate change adaptation was observed ‘Saline tolerant sugarcane variety ISWARDI-40 cultivation’ with ACAPI value of 37.3. The highest proportion (82.3 percent) of the farmer had medium adoption of practices, while 11.5 percent had high and only 6.3 percent had low adoption of climate change adaptation practices. Among the nine selected characteristics of the farmer’s education, annual income, organizational participation and training received showed positive relationship with adoption of climate change adaptation practices; while their age, family size, farm size aspiration and climate change awareness had no significant relationships. ‘Lack of knowledge regarding modern agricultural technologies’ (64.58 percent) emerged as the most important problem expressed by the farmers. The foremost suggestion cited by the farmers (54.17 percent) was ‘Organizing more training program for the farmers’. Community involvement should be emergency to practice the climate change adaptation to the study area. So, it’s the demand of time to establish something or some policy to take them in action. Progressive Agriculture 30 (3): 253-262, 2019